2018
DOI: 10.14419/ijet.v7i4.12.20988
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Thermohydraulic Properties of Nano-Refrigerants

Abstract: The nano-particles achieved the focus of the researchers in the field of refrigeration, due to its capability to change the properties of refrigerants upto a large extent. Nanofluids based on refrigerant is known as nano refrigerants and provided an improvement in thermophysical properties of various refrigerants in different terms. Different theoretical and experimental models are provided by the researchers have been used for the evaluation of different properties of refrigerant in terms of thermal conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Similarly, Nair et al 20 measured the density of Al 2 O 3 /R134a with the particle concentration varying from 0.1% to 0.5% and the values are ranged between 968.72 and 971.65 kg m −3 . Parkash et al 21 revealed the dependency of density with the temperature at various volume concentrations of ZnO nano-sized particles in R134a. However, Maheshwary et al 22 studied the influence of shape on the density of ZnO nanoparticles suspended in R134a refrigerant.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Nair et al 20 measured the density of Al 2 O 3 /R134a with the particle concentration varying from 0.1% to 0.5% and the values are ranged between 968.72 and 971.65 kg m −3 . Parkash et al 21 revealed the dependency of density with the temperature at various volume concentrations of ZnO nano-sized particles in R134a. However, Maheshwary et al 22 studied the influence of shape on the density of ZnO nanoparticles suspended in R134a refrigerant.…”
Section: Introductionmentioning
confidence: 99%